ESTIMASI POTENSI TEGAKAN HUTAN HASIL INVENTARISASI DI PULAU BUANO KABUPATEN SERAM BAGIAN BARAT - Yulianus Dominggus Komul (Jurnal Sylva Scienteae, 2023)
Estimation of Forest Stand Potential from Inventory in Buano Island, West Seram District. This research was carried out with the aim of knowing the potential and types of wood based on the quality class of timber forest products in the Protection Forest of Buano Island which had been established in 2014 through SK No.854/Menhut-II/2014. This study used data from a timber forest inventory in collaboration with the Department of Forestry and the Maluku Development Participation Institute for 2020. From observations on an area of 60,000 m2 or 6 ha, 64 types of tree stands were found divided into 26 families with a total of 996 individual species. The species with the highest number of individuals found were Red Wood or Arawala (Eugenia sp) from the Myrtaceae family, Nutmeg Small leaf Forest (Myristica brassi) from the Myristicaceae family, Makila (Litsea angulata) from the Lauraceae family, Crocodile skin or Asali (Eugenia sp) from family Myrtaceae and Gofasa or Pasane (Vitex cofasus) from the family Verbenaceae. Potential stands consist of 2421.7 m3 with an average tree volume for the entire population in the study area of 220.08 m3. The species Linggua (Pterocarpus indicus), Kayu Besi (Instia bijuga), and Pulaka (Octomeles sumatrana) are commercial species 1, have small populations in each observation plot, but have stem diameters >50 cm Up so that they affect the volume of trees obtained individually as well as the average in the study areaEstimasi Potensi Tegakan Hutan Hasil Inventarisasi di Pulau Buano Kabupaten Seram Bagian Barat. Penelitian ini dilaksanakan dengan tujuan untuk mengetahui potensi serta jenis kayu berdasarkan kelas kualitas dari hasil hutan kayu pada Hutan Lindung Pulau Buano yang telah ditetapkan pada tahun 2014 melalui SK No.854/Menhut-II/2014. Penelitian ini menggunkan data hasill inventarisasi hutan kayu kerjasama Jurusan Kehutanan dan Lembaga Partisipasi Pembangunan Maluku Tahun 2020.  Hasil pengamatan pada luasan 60.000 m2 atau 6 ha, ditemukan 64 jenis tegakan pohon yang terbagi kedalam 26 family dengan jumlah spesies sebanyak 996 individu. Jenis dengan jumlah individu terbanyak yang  dijumpai adalah Kayu Merah atau Arawala (Eugenia sp) dari family Myrtaceae, Pala Hutan daun Kecil (Myristica brassi) dari family Myristicaceae, Makila (Litsea angulata) dari family Lauraceae, Kulit buaya atau Asali (Eugenia sp) dari family Myrtaceae dan Gofasa atau Pasane (Vitex cofasus) dari famili Verbenaceae. Potensi tegakan terdiri atas 2421,7 m3 dengan rata rata volume pohon untuk keseluruhan populasi pada wilayah penelitian  adalah 220,08 m3. Jenis Linggua (Pterocarpus indicus), Kayu Besi (Instia bijuga), dan Pulaka (Octomeles sumatrana) merupakan jenis komersil 1, memiliki populasi yang sedikit pada setiap plot pengamatan, namun memiliki diameter batang >50 cm Up sehingga mempengaruhi volume pohon yang diperoleh secara individu maupun rata rata dalam kawasan penelitian